Herpesvirus Infections in KIR2DL2-Positive Multiple Sclerosis Patients: Mechanisms Triggering Autoimmunity - Bortolotti, Daria; Gentili, Valentina; Bortoluzzi, Alessandra; Govoni, Marcello; Schiuma, Giovanna; Beltrami, Silvia; Rizzo, Sabrina; Baldi, Eleonora; Caselli, Elisabetta; Pugliatti, Maura; Castellazzi, Massimiliano; Fernández, Mercedes; et al. (Microorganisms (Basel), 2022)
In multiple sclerosis (MS), there is a possible relationship with viral infection, evidenced by clinical evidence of an implication of infectious events with disease onset and/or relapse. The aim of this research is to study how human herpesvirus (HHVs) infections might dysregulate the innate immune system and impact autoimmune responses in MS. We analyzed 100 MS relapsing remitting patients, in the remission phase, 100 healthy controls and 100 subjects with other inflammatory neurological diseases (OIND) (neuro-lupus) for their immune response to HHV infection. We evaluated NK cell response, levels of HHVs DNA, IgG and pro- and anti-inflammatory cytokines. The results demonstrated that the presence of KIR2DL2 expression on NK cells increased the susceptibility of MS patients to HHV infections. We showed an increased susceptibility mainly to EBV and HHV-6 infections in MS patients carrying the KIR2DL2 receptor and HLA-C1 ligand. The highest HHV-6 viral load was observed in MS patients, with an increased percentage of subjects positive for IgG against HHV-6 in KIR2DL2-positive MS and OIND subjects compared to controls. MS and OIND patients showed the highest levels of IL-8, IL-12p70, IL-10 and TNF-alpha in comparison with control subjects. Interestingly, MS and OIND patients showed similar levels of IL-8, while MS patients presented higher IL-12p70, TNF-alpha and IL-10 levels in comparison with OIND patients. We can hypothesize that HHVs’ reactivation, by inducing immune activation via also molecular mimicry, may have the ability to induce autoimmunity and cause tissue damage and consequent MS lesion development.